Organ and gestational age effects of maternal nutrient restriction on global methylation in fetal baboons - Unterberger, Alexander (2009)
A sub-optimal intrauterine environment alters the trajectory of fetal development with profound effects on life-time health. Altered methylation, a proposed epigenetic mechanism responsible for these changes, has been studied in non-primate species but not nonhuman primates. We tested the hypotheses that global methylation in fetal baboon demonstrates organ specificity, gestational age specificity, and changes with maternal nutritional status. We measured global DNA methylation in fetuses of control fed (CTR) and nutrient restricted mothers fed 70% of controls (MNR) for brain, kidney, liver and heart at 0.5 and 0.9 gestation (G). We observed organ and gestation specific changes that were modified by maternal diet. Methylation in CTR fetuses was highest in frontal cortex and lowest in liver. MNR decreased methylation in 0.5G kidney and increased methylation in 0.9G kidney and frontal cortex. These results demonstrate a potential epigenetic mechanism whereby reduced maternal nutrition has long-term programming effects on fetal organ development.